(untitled) (Fiep Bulletin - online, 2019)
Nutrition and anthropometric profile are important factors for the performance of physical fitness. Regardless ofphysical activity, nutritional behaviors are determinant in maintaining health, increasing performance and controlling bodycomposition. Therefore, this study aims to analyze the anthropometric and ingestion profile of the participants of the FIP FITNESacademy. This is a documentary and quantitative survey. The sample consisted of 33 evaluation cards answered and analyzed inthe year 2017. From these records the variables for identification of the nutritional aspects and for the anthropometric profile wereevaluated, the following variables were evaluated: BMI, average fat percentage obtained through of skin folds, weight andcircumference measurements, body composition assessment; intake profile; where it feeds and quantity of meals during the day,food builders, energy foods, food regulators, cryogenic auxiliaries. The analysis of the assigned data will be applied to descriptivestatistics and the data will be computed in Excel. Research individuals feed on the majority at home having about 4 to 5 meals aday with a low water intake, a good amount of protein choices, almost everyone has rice or beans or both in their meal ascarbohydrates, consume It is concluded that these data add positively on the anthropometric data since the BMI was good alongwith the body composition.